2021
DOI: 10.3389/fonc.2021.731752
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis and Identification of Dysregulated Panel lncRNAs Contributing to Poor Prognosis in Head-Neck Cancer

Abstract: Head and neck cancer (HNC) is one of the most prevalent cancers worldwide, accounting for approximately 5% of all cancers. While the underlying molecules and their pathogenetic mechanisms in HNC have yet to be well elucidated, recent studies have shown that dysregulation of lncRNAs may disrupt the homeostasis of various biological pathways. However, the understanding of lncRNAs in HNC is still limited by the lack of expression profiling. In the present study, we employed a systematic strategy to identify a pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…However, these arrays allow sensitive, specific, and rapid data analysis. Previous studies have reported the use of PCR arrays to analyze genes in specific diseases, such as cancers [ 33 ]. In this study, we employed a PCR-based array to analyze 84 cancer-associated lncRNAs in areca nut-treated HNC cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these arrays allow sensitive, specific, and rapid data analysis. Previous studies have reported the use of PCR arrays to analyze genes in specific diseases, such as cancers [ 33 ]. In this study, we employed a PCR-based array to analyze 84 cancer-associated lncRNAs in areca nut-treated HNC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Human Cancer PathwayFinder RT2 PCR array system consisting of 84 cancer-related lncRNA assays was used for lncRNA screening (QIAGEN GmbH, Hilden, Germany). The lncRNA PCR array was performed according to the manufacturer’s protocol as previously described [ 33 ]. Briefly, cell pellets were harvested, washed with PBS, and subjected to RNA isolation using TRIzol reagent (Life Technologies, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oncogenic lncRNAs, which are upregulated in cancer, are expected to be diagnostic markers, prognostic factors, and even novel therapeutic molecular targets [43]. HOXA11AS is one of the 16 most dysregulated lncRNAs in head and neck cancer and has attracted attention as a therapeutic target [44]. Attempts to apply lncRNA targeting to therapy have included the use of antisense oligonucleotides and small molecules to block the functional interactions between lncRNAs and proteins, and inactivation of lncRNA-encoding genes and the transcripts based on the CRISPR-Cas system are under development [45].…”
Section: Discussionmentioning
confidence: 99%